RESPON PERTUMBUHAN SEMAI GAHARU (Aquilaria malaccensis) TERHADAP PEMBERIAN PUPUK DAUN GREEN TONIK DI SHADE HOUSE FAKULTAS KEHUTANAN BANJARBARU - Sri Hartatik; Damaris Payung; Normela Rachmawati (Universitas Lambung Mangkurat, 2020)
Indonesia is the largest producer of gaharu in the world, until the end of 1990 it was able to produce more than 600 tons per year, since 2000 production continued to decline and with a quota of around 300 tons/year it was only able to meet 10-15%, even since 2004 with a quota of 50 - 150 tons/year, there is no record of exports of gaharu from Indonesia. The purpose of this study was to measure the survival percentage of gaharu seedlings, analyze the growth response of gaharu seedlings to the administration of green tonic leaf fertilizer, and determine the dosage of green tonic leaf fertilizer which can provide the best growth for gaharu seedlings. The results obtained from the study are the percentage of gaharu seedlings in each treatment categorized as successful because it lives 100%. Treatment D, namely the administration of green tonic leaf fertilizer with a dose of 7 ml/l of water member growth was better than the other treatments based on the increase in height, diameter and number of leaves in gaharu seedlings. Keywords: Gaharu; fertilizer; green tonic